Breaking the bonds of racism - Lindsey, Paul 1924; Lindsey, Ouida 1927 (Homewood, Ill. : ETC Publications, 1974)
Describes the lifestyle of blacks in the United States--including the problems of housing, economics, stereotypes--and the perspectives of both blacks and whites regarding education and learning.
Bibliography: p. 219-228.
Keywords: African Americans -- Education; School integration -- United States